Comparison of Deictic Gestures in Tamil-Speaking Toddlers at Risk for Autism Spectrum Disorder and Typically Developing Peers - Monish V; S. PowlinArockia Catherine; MK Rajasekar (Journal of Rehabilitation)
Objective Deictic gesture use is important for children at an early age with autism spectrum disorders (ASD) in the development of spoken language. The most frequently used deictic gestures are reaching, pointing, showing, and giving. This study aims to compare the production of deictic gestures in Tamil-speaking toddlers at risk for ASD and their typically developing (TD) peers. Materials & Methods Participants in this study included 45 Tamil-speaking toddlers ("with developmental age of 12-36 months") and their parents. They were put in three groups of ASD (n=15), TD-DA (n=15, matched for age at mental development and gender), and TD-LA (n=15, matched for age at language development and gender). The parents received instruction to play with their children like they were playing at home, using a set of toys given to them, and this session was video recorded. The Eudico Linguistic Annotator (ELAN) was used to analyze the deictic gestures (reaching, pointing, giving, and showing) and their subtypes. Results There were significant differences between the ASD and TD-DA groups (P=0.025) and between the ASD and TD-LL groups (P=0.014) in producing overall deictic gestures. The ASD group produced fewer deictic gestures (Mean=17.20) during dyadic interaction than the TD-DA (Mean=25.60) and TD-LL (Mean=29.46) groups. The most frequently produced deictic gesture type by the ASD group was reaching (Mean=15.13) followed by pointing (Mean=1.20), giving (Mean=0.86), and showing (Mean=0.20). Conclusion Tamil-speaking children at risk for ASD have deficits in the production of deictic gestures such as pointing, giving, and showing compared to their TD peers. The findings underscore the importance of assessing the deictic gestures produced by toddlers at risk for ASD, as well as their other communication abilities, which can help in planning for assessment and intervention.